Recent progress in syngas production via catalytic CO2 hydrogenation reaction - Bahmanpour, Ali M.; Signorile, Matteo; Kröcher, Oliver (Applied catalysis. B, Environmental, 2021)
[Display omitted] •Recent advances in catalyst design for the RWGS reaction are studied.•CO adsorption energy in transition metals may affect their CO2 hydrogenation product selectivity.•Different reaction mechanisms for the RWGS reaction are proposed.•Electron density, catalyst structure, and the presence of hydroxyl groups are vital for catalyst design. Synthesis gas production through the catalytic reverse water-gas shift (RWGS) reaction is an attractive option for the conversion of CO2 to fuels. Many metal-based catalysts have been introduced for this reaction in order to provide high activity, CO selectivity, and stability. Recently, progress has been made in catalyst design and understanding of the reaction mechanism, which has shed light on the characteristics of the catalysts needed for this reaction. Accordingly, new noble and non-noble metal-based catalysts with remarkable performance have been introduced for this reaction. However, there is still much room for catalyst improvement specifically in regard to catalyst stability at the high temperatures required for this reaction. There are also controversial arguments regarding the active sites of the reaction. This review highlights the recent progress in catalyst design and understanding of the reaction mechanism for the RWGS reaction and derives proposals for further improvements of the process.